Establishing a Gynecology Student-Run Free Clinic: A Joint Medical Student and Resident Physician Initiative - Lee, David; Loh, Tiffany; Blackmond, Nicholas; George, Sarah; Fong, Felicia; Quach, Kaitlyn; Franz, Patricia; Wharton, Kurt (Journal of Student-Run Clinics, 2024)
Dedicated women’s health services are rarely mentioned in the student-run free clinic literature. As society grappled with repeated waves of coronavirus-2019, the number of healthcare professionals decreased across the country and impacted all healthcare settings, including student-run free clinics. In response, a collaboration between medical students and Obstetrics & Gynecology resident physicians at Oakland University William Beaumont School of Medicine and the Gary Burnstein Community Health Clinic established a new gynecology free clinic. This program, under the joint oversight of medical students and resident physicians in addition to attending physician support, provided uninsured women across Southeast Michigan with critical access to healthcare services at a time demand for services was similarly rising. Our clinic emphasized excellence in screening, contraception, and vaccination and, in doing so, provided our patients with evidence-based care and a medical home. Our experience demonstrates student-run free clinics are uniquely positioned to critically expand access to women’s health services. Additionally, the establishment of a joint medical student and resident physician endeavor can further enrich both the educational and patient-care experience.